The Changing Pattern of Homicide in Ireland - Brady , Bernadette; Clarke, Lindsey (Trinity Student Medical Journal, 2006)
Objective: To study the pattern of homicides (encompassing both murder and manslaughter) in the Republic of Ireland in the years 1994 and 2004. Methods: Data was obtained from the Office of the State Pathologist, the Technical Bureau of An Garda Siochána and the Central Statistics Office. Results: Approximately three-quarters of victims were found to be male in both 1994 and 2004. In 1994, 100% of victims were of Irish nationality compared with 85% of Irish nationality in 2004. 16 of 24 total homicides in 1994 were in County Dublin, with 21 of 45 total homicides taking place in the same county in 2004. Gunshot wounds accounted for 8 of a total 24 deaths by homicide in 1994, while blunt force trauma and stab wound(s) each accounted for 10 of a total 45 deaths by homicide in 2004. Conclusion: The proportion of male homicide victims has remained stable over the 1994 to 2004 period, while the percentage of non-Irish homicide victims has risen by 15%. Dublin was the county with the most homicides in both 1994 and 2004. The primary mode of homicide changed from gunshot in 1994 to lone blunt force trauma and lone stab wound(s) in 2004.